1983
DOI: 10.1007/bf00270175
|View full text |Cite
|
Sign up to set email alerts
|

Studies on tissue cultures of the genus Cinchona L.

Abstract: A procedure for the in vitro clonal mass propagation of shoots and plants of two Cinchona species derived from single shoot tips is described. Special attention is given to rooting problems of the shoots under in vitro conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…This work led to the formulation of a medium (C19) containing levels of 2,4-D (0.5 mg 11) and BA (0.1 mg 1') in which growth and alkaloid production were maintained over an extended period of culture. The levels of alkaloid produced de tovo by cells growing in this medium compared favourably with those found by other workers using suspension cultures of C. ledgeriana (2) and C. pubescens (3). Although in callus it has been found that the level and type of alkaloid present (4, 5) may be manipulated by altering the amounts of plant growth regulators present, no attempt has previously been made to optimise their effect.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…This work led to the formulation of a medium (C19) containing levels of 2,4-D (0.5 mg 11) and BA (0.1 mg 1') in which growth and alkaloid production were maintained over an extended period of culture. The levels of alkaloid produced de tovo by cells growing in this medium compared favourably with those found by other workers using suspension cultures of C. ledgeriana (2) and C. pubescens (3). Although in callus it has been found that the level and type of alkaloid present (4, 5) may be manipulated by altering the amounts of plant growth regulators present, no attempt has previously been made to optimise their effect.…”
Section: Introductionsupporting
confidence: 74%
“…Cultures of Cinchona have been established in a number of laboratories (2)(3)(4)(5)(6)(7)(8)(9)(10)(11); methods for the multiplication of shoots (2) and the regeneration of whole plants from single shoot tips (3) have been developed. In the initial work on the production of alkaloids in culture (2, 4), significant production was found in organised leaf cultures (2) but not in unorganised suspension cultures (4).…”
Section: Introductionmentioning
confidence: 99%
“…Krikorian et al (5) reported the aseptic micropropagation of C. ledgeriana shoot cultures and Noerhadi (6) the establishment of cinchona callus. Koblitz et al (7) reported an in vitro clonal mass propagation procedure for C. ledgeriana and C. succirubra shoots derived from plant shoot-tips. The rooting capacity of shoots on a zeatin containing medium was higher than those cultivated on BA.…”
Section: Introductionmentioning
confidence: 99%